In vivo electrophysiological study of vitamin D3 protective effects on PTZ-induced seizures in rats - Sara Hosseinchi Gharehaghaji; Yousef Panahi; Emad Khalilzadeh; Gholamreza Vafaei Saiah (Wolters Kluwer Medknow Publications, 2023)
Background and purpose: The purpose of the current study was to investigate the protective effects of acute and chronic administration of different doses of vitamin D3 on pentylenetetrazol (PTZ)-induced epileptiform activities in rats. Experimental approach: Sixty Wistar rats in chronic and acute groups were used in this study. In the chronic groups, animals received vitamin D3 at 50, 100, and 150 μg/kg; vitamin D3 (50 μg/kg, i.p.) + diazepam (0.1 mg/kg, i.p.), and almond oil (i.p.) daily for two weeks whereas, in the acute groups the animal received a single dose of chemicals just 30 min before PTZ administration. The electrophysiological recording was performed by implanting a unilateral bipolar electrode in the pyramidal cell layer of the CA1 region of the hippocampus. Epileptic activities were induced by intraperitoneal injection of PTZ (80 mg/kg, i.p.). The spike count and amplitude were analyzed using the eTrace software. Finding/Results: Chronic administration of all doses of vitamin D3 and its combination with diazepam significantly reduced both spike counts and amplitudes following PTZ administration. While the acute doses were ineffective. Conclusion and implication: The results of the study indicated that chronic but not acute administration of vitamin D3 has a protective effect on PTZ-induced epileptiform activity in rats.